2021
DOI: 10.1002/jgh3.12653
|View full text |Cite
|
Sign up to set email alerts
|

The unmet needs for identifying the ideal bowel preparation

Abstract: Colonoscopy, since it was first employed over 60 years ago, is now the gold standard method for visualizing the mucosa of the colon, but should be of good quality. Many factors affect quality, including the type of health service organization, type of facility, staff, equipment, patient characteristics, and bowel preparation (BP). The adequacy of bowel cleansing is critical, but, unfortunately, may be inadequate in up to one‐third of procedures. The current article will present and discuss the main BPs and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
(139 reference statements)
0
10
0
3
Order By: Relevance
“…Adequacy of bowel preparation depends on different factors, either related to the patient or to the preparation itself [5,6]. Among factors related to the cleansing products, volume of preparation, and the modality of assumption are particularly relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequacy of bowel preparation depends on different factors, either related to the patient or to the preparation itself [5,6]. Among factors related to the cleansing products, volume of preparation, and the modality of assumption are particularly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Today, however, international guidelines [4,5] recommend different types of bowel preparations, without indicating specific recommendations to guide physicians on which one to choose. The main distinction among the different products is the volume of liquids to be assumed by the patient [6].…”
Section: Introductionmentioning
confidence: 99%
“…Die optimale Vorbereitung von Diabetes-Patienten vor einer Koloskopie gibt es nicht "von der Stange". Sie erfüllt vielmehr die Kriterien einer personalisierten Medizin [31]…”
Section: Konzepte Zur Darmvorbereitung Vor Koloskopieunclassified
“…Several factors such as the institutional cadre, personnel, hospital stay length, patient characteristics, and bowel preparation efficiency can affect the outcomes of colonoscopy. 12 Adequate bowel preparation is one of the most important requirements for achieving high-quality colonoscopic findings. Many studies have reported that a considerably higher proportion of patients undergoing colonoscopy have inadequate bowel preparation.…”
Section: Introductionmentioning
confidence: 99%